The dialectic between deciduous and coniferous forests in central Iberia: A palaeoenvironmental perspective during the late Holocene in the Gredos range. (15th March 2018) - Robles-López, Sandra; Fernández Martín-Consuegra, Aitor; Pérez-Díaz, Sebastián; Alba-Sánchez, Francisca; Broothaerts, Nils; Abel-Schaad, Daniel; López-Sáez, José Antonio
Abstract: Pollen analyses supported by fifteen AMS 14 C dates from Fuente de la Leche (1382 m) and Fuente del Pino Blanco (1343 m) peat sequences, in the Gredos range (central Spain), are used to reconstruct the late Holocene vegetation history in this mountain region. These results are compared with other sequences from the Spanish Central System in order to better understand the past dynamics of the main forest constituents and to provide a critical view of the dialectic between conifers and deciduous forests. The vegetation record at Fuente de la Leche starts at 3000 cal yr BP, with the occurrence of rather closed forests composed of Pinus sylvestris and Betula . Pinus sylvestris was the dominant pollen taxa for almost the entire period. However, during the last 850 years, Pinus sylvestris forests were progressively replaced by Quercus pyrenaica woodlands and grasslands, as a result of a high pastoral pressure, until forming mixed woodlands ∼400 years ago. The interpretation of Fuente del Pino Blanco record is that dramatic changes started about 265 years ago. Prior to this date, an open canopy woodland included species ( Alnus glutinosa, Quercus pyrenaica ) whose distributions no longer exist in the studied area. We suggest that the increase in agricultural (rye and other cereals) and livestock activities forced a change in the role of fire in the supramediterranean belt of the Gredos range, thus Pyrenean oak canopy was consumed by fires, providing openings for Pinus pinaster and broom communities better adapted to fire.